2018
DOI: 10.3389/fphar.2018.00799
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral TDF-Based Pre-exposure Prophylaxis for Men Who Have Sex With Men: A Systematic Review and Meta-Analysis

Abstract: Background: Pre-exposure prophylaxis (PrEP) is used as an HIV prevention method by people at substantial risk of HIV infection. This systematic review and meta-analysis evaluates current clinical evidence for use of oral TDF-based PrEP among men who have sex with men.Methods: A comprehensive literature search in PubMed, web of science, Google Scholar and ClinicalTrials.gov was performed. A random-effects meta-analysis was conducted using the event rate (ER) for estimation of the incidence of HIV and grade 3 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 40 publications
1
33
0
4
Order By: Relevance
“…Low levels of PrEP awareness have been consistently reported in the Chinese MSM community . Although many studies have demonstrated that oral Tenofovir‐based PrEP regimens are effective and safe among MSM , a considerable proportion of our sample was concerned about PrEP's efficacy (56.8%) and potential side effects (69.9%). These two concerns emerged as more notable barriers to PrEP adoption within our study sample than within other study samples in Asia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Low levels of PrEP awareness have been consistently reported in the Chinese MSM community . Although many studies have demonstrated that oral Tenofovir‐based PrEP regimens are effective and safe among MSM , a considerable proportion of our sample was concerned about PrEP's efficacy (56.8%) and potential side effects (69.9%). These two concerns emerged as more notable barriers to PrEP adoption within our study sample than within other study samples in Asia.…”
Section: Discussionmentioning
confidence: 85%
“…Adjusted ORs for PrEP knowledge and PrEP uptake preferences among men participated in the China MSMs HIV PrEP Uptake Willingness Online Survey, 2017 (N = 4581) PrEP uptake "Definitely yes" AOR (95% CI) "Probably yes" AOR (95% CI) MSM community [30,31]. Although many studies have demonstrated that oral Tenofovir-based PrEP regimens are effective and safe among MSM [37], a considerable proportion of our sample was concerned about PrEP's efficacy (56.8%) and potential side effects (69.9%). These two concerns emerged as more notable barriers to PrEP adoption within our study sample than within other study samples in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, PBMCs were isolated from fresh blood collected from four healthy HIV-negative donors by density gradient centrifugation. 77 PBMCs were resuspended to 1×10 6 Louis, Missouri, USA) was used as the positive control, at a final concentration of 10 µg/mL. The CCR5-tropic HIV-1 NL4-3 AD8 78 was used at an multiplicity of infection (MOI) of 0.9, as previously described.…”
Section: Materials and Methods Isolation And Culture Of Pbmcs With Hivmentioning
confidence: 99%
“…Zahlreiche Studien belegen die Wirksamkeit der PrEP [6][7][8][9]. Seit 2017 existiert im WIR -Walk In Ruhr -Zentrum für sexuelle Gesundheit und Medizin ein innovatives Modellprojekt zur intersektoralen PrEP-Versorgung (.…”
Section: Hiv-präexpositionsprophylaxe-versorgung In Intersektoraler Zunclassified